Perencana yang Profesional dan Modern: Meningkatkan Peran Perencana dalam kerangka Perspektif Jangka Panjang Penjabaran Visi Indonesia 2045 - Dadang Solihin (Kementerian Perencanaan Pembangunan Nasional (Bappenas), 2020)
This policy paper carries the theme: Towards Professional Planners in the Termination of Stages of RPJPN 2005-2025 and Determination of Strategy for Implementing Indonesia's Vision 2045. With Sub-themes: Increasing the Role of Planners in the Long-Term Perspective Framework for the Indonesian Vision 2045. It is concluded that there are three problems faced in increasing the role of planners in the framework of the elaboration of the Indonesian Vision 2045, as well as in preparing policy recommendations to realize professional planners. The three problems are the lack of understanding of JFP regulations, the existence of